Germany - Gray, Susan Heinrichs (New York Children's Press, 2003)
Presents information on the geography, history, people, economy, and social life and customs of Germany, one of the largest countries in Europe
Hurg
5 8
Keywords: Germany -- History -- Juvenile literature; rmany -- Juvenile literature